2018
DOI: 10.1097/mlr.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Eliminating Copayments for Tobacco Cessation Pharmacotherapy

Abstract: Objectives: We examined the impact of the Affordable Care Act (ACA) mandated elimination of tobacco cessation pharmacotherapy (TCP) copayments on patient use of TCP, overall and by income. Methods: Electronic health record data captured any and combination (e.g., nicotine gum plus patch) TCP use among adult smokers newly enrolled in Kaiser Permanente Northern California (KPNC). KPNC eliminated TCP copayments in 2015. We included current smokers newly enrolled in the first 6 months of 2014 (before copayment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(36 reference statements)
0
9
1
Order By: Relevance
“…Third, accounting for language and light/non-daily smoking, there were few differences in receipt of quit smoking advice, knowledge of smoking cessation classes/counseling and free pharmacotherapy, or use of cessation treatments by age, race/ethnicity, insurance coverage, or median household income, suggesting that healthcare reform may have helped to equalize access to and use of tobacco treatments for many at-risk groups. These findings differ from our prior study of non-Medicaid patients, which found lower knowledge about free cessation pharmacotherapy among lower income commercially insured patients (Young-Wolff et al, 2018), suggesting that Medicaid patients may have greater awareness that pharmacotherapy is free than commercially insured patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Third, accounting for language and light/non-daily smoking, there were few differences in receipt of quit smoking advice, knowledge of smoking cessation classes/counseling and free pharmacotherapy, or use of cessation treatments by age, race/ethnicity, insurance coverage, or median household income, suggesting that healthcare reform may have helped to equalize access to and use of tobacco treatments for many at-risk groups. These findings differ from our prior study of non-Medicaid patients, which found lower knowledge about free cessation pharmacotherapy among lower income commercially insured patients (Young-Wolff et al, 2018), suggesting that Medicaid patients may have greater awareness that pharmacotherapy is free than commercially insured patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, persistent inequalities in receiving cessation advice among light/non-daily smokers, Hispanics/Latinos, young adults, low-income adults, and uninsured smokers remained (Tan et al, 2018). Further, 30-day smoking prevalence declined and pharmacotherapy fills increased in states that expanded Medicaid (Young-Wolff et al, 2018; Simon et al, 2017; MacLean et al, 2017). Our prior work with smokers enrolled in California exchange or non-exchange commercial plans found that the ACA's elimination of pharmacotherapy copayments was associated with a small increase in pharmacotherapy prescription fills with a greater effect among lower-income smokers (Young-Wolff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…68 Evidence shows an increase in zero copay claims for preventive medications and their utilization rates. 69,70…”
Section: Data Synthesismentioning
confidence: 99%
“…68 Evidence shows an increase in zero copay claims for preventive medications and their utilization rates. 69,70 In 2006, about 35% of prescription drug expenditures were paid out of pocket among the US population <65 years old. 71 In 2018, the total out-of-pocket expenditure on prescription drugs was 61 billion dollars, which is about 17% of total net prescription medication spending.…”
Section: Increase In Proportion Of Prescriptions Covered By Insurancementioning
confidence: 99%
“…[5][6][7][8] There is evidence that some women use cannabis to alleviate pregnancy-related symptoms (e.g., nausea and vomiting) and to self-medicate symptoms of depression, anxiety, or pain. 6,[9][10][11][12][13][14][15] However, due to concerns about health risks, including low infant birthweight and potential impacts on offspring neurodevelopment, [16][17][18][19] the American College of Obstetricians and Gynecologists currently recommends that pregnant women abstain from using cannabis during pregnancy and while breastfeeding. 20 An integrative review of women's perceptions of the health effects of prenatal cannabis use found that perceived harms of cannabis use in general are decreasing over time, 8 and some pregnant women who use cannabis perceive no health risks.…”
Section: Introductionmentioning
confidence: 99%